The Indian net-casting spider name Deinopis goalparaensis Tikader & Malhotra is a nomen dubium (Araneae: Deinopidae) - Caleb, John T.d. (Zootaxa, 2019)
The genus Deinopis was established by MacLeay (1839) with D. lamia MacLeay, 1839 as its type species. It is the most speciose deinopid genus presently comprising 51 described species, of which two are known from India (World Spider Catalog 2019). The genus was first recorded from India with the description of the species, Deinopis goalparaensis Tikader and Malhotra, 1978 from Assam, which was described based on the females only (Tikader & Malhotra 1978) and the male still remains unknown. Thirty-six years later another species, Deinopis scrubjunglei Caleb & Mathai, 2014 was described from Chennai, Tamil Nadu based on both sexes (Caleb & Mathai 2014). Apart from these taxonomic accounts, Satam et al. (2015) provided notes on the microhabitat utilization of juvenile Deinopis spiders from Mumbai. With no other supportive studies and additional data on these spiders, Indian deinopids remain obscure and inadequately known. The goal of the present communication is to provide clarification on the taxonomic status of the poorly known Indian species D. goalparaensis, supported with illustrations.